Effect of Gamma Radiation on Protein Content of Honey Bee Queen After Mating (Apis mellifera) (Journal of Nuclear Technology in Applied Science, 2025)
This study investigated the effects of low doses of gamma irradiation on the  biological activity and fertility of honeybee queens (Apis mellifera) by examining  brood production and protein profiles. Queens exposed to 20 and 30 rad showed a  significant increase in brood area, with the 20 rad dose yielding the highest mean  brood area, reflecting a stimulatory effect on reproductive activity. In contrast,  higher doses of 40 and 50 rad caused a marked decline in brood production,  suggesting a threshold beyond which radiation becomes detrimental. Biochemical  analyses revealed that total protein content was highest at 20 rad, with a gradual  decrease at higher doses, indicating dose-dependent effects on protein synthesis  or stability. Electrophoretic profiling confirmed these biochemical changes,  showing enhanced protein band intensity and diversity at low radiation levels and  suppression at higher doses. Overall, the findings suggest that sub-lethal doses of  gamma radiation can enhance certain physiological and reproductive functions  in honeybee queens, while excessive exposure impairs these processes.
Keywords: Apis mellifera Honeybee queen-Gamma irradiation-Protein analysis.